(untitled) (Research, Society and Development, 2024)
Understanding the relationship between food choices and mental health has gained prominence in a global context marked by increasing challenges such as stress, anxiety, and depression. This study investigated this connection, examining how diet impacts not only physical health but also mental health. Thus, the aim of this work was to demonstrate the relationship between diet and mental health, focusing on the role of nutrients in promoting psychological well-being and enhancing cognitive performance. This study is a literature review and sought to synthesize and analyze previous research on the influence of diet on mental health and cognitive performance. The approach is exploratory and aims to consolidate evidence to enrich understanding of the topic. The methodology adopted consists of a systematic literature review, with a comprehensive analysis of studies published in scientific databases such as SCIELO, PUBMED and SCIENCE DIRECT. The research prioritized scientific articles, systematic reviews, and meta-analyses that address the relationship between diet, lifestyle, mental health, and cognitive performance. The critical analysis of these studies contributes to achieving the proposed objectives, providing a comprehensive and updated view of the field. Studies, in general, demonstrate that diets rich in saturated fats and sugar can impair brain performance, altering the functioning of the hippocampus and compromising functions such as memory and learning. Furthermore, it shows how proper nutrition is directly linked to the prevention of mental health disorders and brain functioning.